“Sightblind”: Perceptual Deficits in the “Intact” Visual Field - Bola, Michal; Gall, Carolin; Sabel, Bernhard A. (Frontiers in Neurology, 2013)
Unilateral visual cortex lesions caused by stroke or trauma lead to blindness in contralateral visual field – a condition called homonymous hemianopia. Although the visual field area processed by the uninjured hemisphere is thought to be “intact”, it also exhibits marked perceptual deficits in contrast sensitivity, processing speed, and contour integration. Such patients are “sightblind” - their blindness reaches far beyond the primary scotoma. We review studies showing perceptual deficits in patients’ intact fields and discuss the implications of these findings. We conclude that the consequences of partial blindness are greater than previously thought, as perceptual deficits in the “intact” field likely contribute to subjective vision loss in patients with visual field defect. This has important implications for vision diagnosis and rehabilitation.